HISTOPATHOLOLOGICAL STUDY ON THE EFFECTS OF TEXTILE EFFLUENTS IN THE GILLS OF FRESH WATER FISH, COMMON CARP CYPRINUS CARPIO (LINN.) - R.KOWSALYA; C.M.KARRUNAKARAN; M.DEECARAMAN; A.UMA; SWARANJIT SINGH (International Journal of Pharma and Bio Sciences, 2013)
The effect of textile effluents in Cyprinus carpio (Common carp) was studied by experimental exposure to effluents at three different levels (10%, 15% and 20% v/v).The histopathological changes in the gills of common carp was recorded at day 1, 2, 4 and 7 after exposure to textile effluents. Results showed that textile effluents causes histopathological changes in the gills of Cyprinus carpio which included congestion, fusion of gill lamellae and degeneration of secondary gill epithelium.